Keragaman jenis burung pada kawasan mangrove di Taman Nasional Rawa Aopa Watumohai - Maryatul Qiptiyah; Bayu Wisnu Broto; Heru Setiawan (Jurnal Penelitian Kehutanan Wallacea, 2013)
Bird is one of the important species associated with mangrove vegetation. This study aims to determine the diversity of birds in the mangrove areas of Rawa Aopa Watumohai National Park, Indonesia. Observations were done at 12 points for data collection by scanning field by field method. The results revealed that about 54 bird species was found in the surrounding mangrove, eight types of which species was Sulawesi endemic birds and at least three types of which species was migratory birds. The bird species commonly found was Pergam Laut (Duculabicolor), as many as 63 individuals. Index of bird diversity in the mangrove Rawa Aopa Watumohai National Park was 3.40.